1990
DOI: 10.1007/bf01974395
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose toxicokinetics ofN-nitrosomethylethylamine andN-nitrosomethyl (2,2,2-trideuterioethyl)amine in the rat

Abstract: To investigate the origins of an organotropic shift toward increasing esophageal carcinogenicity and DNA alkylation caused by beta-trideuteration of the hepatocarcinogen, N-nitrosomethylethylamine (NMEA), the single-dose toxicokinetics of NMEA and N-nitrosomethyl(2,2,2-trideuterioethyl)amine (NMEA-d3) has been characterized in 8-week-old male Fischer 344 rats by analysis using high performance liquid chromatography of serial blood samples. An i.v. bolus dose of 0.6 mumol/kg to rats revealed biphasic first orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Kinetic constants for their conversion to the two a-hydroxylation products, acetaldehyde and formaldehyde, by uninduced liver microsomes are summarized in Table II. As was found for the rates of in vivo clearance of NEMA (7), no significant change in K m or V W3X values could be observed on /3-deuteration of the carcinogen.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Kinetic constants for their conversion to the two a-hydroxylation products, acetaldehyde and formaldehyde, by uninduced liver microsomes are summarized in Table II. As was found for the rates of in vivo clearance of NEMA (7), no significant change in K m or V W3X values could be observed on /3-deuteration of the carcinogen.…”
Section: Resultssupporting
confidence: 58%
“…We originally speculated that this shift toward the esophagus resulted from an isotopically-induced retardation of /3-hydroxylation during the first pass through the liver following absorption from the gut of the orally-administered carcinogen, but this proved to be incorrect. Detailed pharmacokinetic studies failed to detect any difference between NEMA and NEMA-d 3 in bioavailability or any other pharmacokinetic parameter, nor was any of the /S-hydroxylation product, N-nitrosomethyl^-hydroxyethyl)amine, found in the blood at a detection limit corresponding to 0.3% of the dose (7). Also, the organotropic shift could not be ascribed to altered excretion of unchanged nitrosamine, as neither NEMA nor NEMA-d 3 could be found in the urine at a level of 0.03% of the dose (7).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…But further studies revealed that the situation is more complex than anticipated. Deuterium substitution may be without influence on activity (Lijinsky & Reuber 1980a;Streeter et al, 1990), change the organotropic carcinogenicity (Turusov et al, 1988), or may even have an inverse effect (Lijinsky & Reuber, 1980b). The absence of an isotope effect in DMPT-d6 has meanwhile also been shown in a carcinogenicity experiment.…”
Section: Sister Chromatid Exchange Rates and Cell Cycle Delay Inducedmentioning
confidence: 99%
“…Subsequently, the resulting N-hydroxymethyl-methylnitrosamine (HMMN) proceeds via a demethylation leading to the formation of methyldiazohydroxide, a strong mono-functional alkylating agent which is able to methylate the bases of DNA to form products like O 6 -methylguanine (O 6 -MeG) and 7-methylguanine (7-mGua) [10][11][12]. In contrast to the widely studies on the bioactivities of NDMA from experimental aspects [12][13][14], there is relatively little theoretical investigation of the mechanistic pathway for further transformation of HMMN. In 1987, Poulsen et al [15] proposed both stepwise and concerted mechanisms for this transformation, shown in Scheme 1a by solid line.…”
Section: Introductionmentioning
confidence: 99%